Pemilihan bahan suapan bagi proses pengacuan suntikan logam berdasarkan kepada kajian sifat reologi - Muhamad, Norhamidi; Jamaludin, Khairur Rijal; M. Amin, Sri Yulis; Ab. Rahman, Mohd. Nizam (Penerbit UTM Press, 2008)
Rheological properties of the metal injection molding (MIM) feedstock prepared with gas atomized 316L stainless steel and, polymethyl methacrylate (PMMA), polyethylene glycol (PEG) and stearic acid as binder have been investigated. Capillary rheometer with die of L/D = 10 was used in the investigation. Coarse and fine stainless steel powders were mixed with binders at powder loading of 64% and 65% volume. All feedstocks exhibit pseudo plastics behaviour as the flow behaviour indexes were less than one, but it is inversely proportional to the powder loading. Moreover, the flow behaviour index of the coarse powder is larger than the fine powder particles. Feedstock 16_64 exhibits higher sensitivity among other feedstocks while 31_65 was least sensitive to the temperature and pressure. However, the sensitivity was alsoinversely proportional to the powder loading. Thus, moldability index of the 31_64 is the best and result shows that powder loading 64% volume gives better moldability to the feedstocks. Finally, the investigation concluded that the feedstocks are suitable to be injection molded because the rheological properties demonstrate a shear thinning when subjected to shear stress. However, feedstock with the powder loading of 64% volume is the most suitable as the moldability index is higher than the 65% volume feedstocks.